Mejoramiento de la fiabilidad en microredes mediante el control robusto de voltaje usando técnicas pasivas de tolerancia a fallos - Chinchuña Toledo, Grace Katerine (2018)
This paper proposes an improvement in reliability in micro-grid about the robust control of voltage to failures of the system using passive methods of tolerance to failures. The proposal is based on the identification of possible failures of the diagnostic system for the internal control model (IMC) to reject the disturbance, as a control strategy. The development of the robust control is based on the voltage of a DC micro-grid, which allows the system to operate in a stable and within the permissible margins of quality against failures in actuators, sensors and the plant without the need to use reconfiguration techniques. Stability in Micro-grid is continuously affected in the related loads. Finally, the results are presented in certain control conditions. This research is illustrated the IEEE 14-nodes system and the Simulink/Matlab where the initial data of the system were obtained proposed method provides robust performance.